Zircon U–Pb and molybdenite Re–Os geochronology and whole‐rock geochemistry of the Baishan porphyry Mo deposit: Insights into Triassic mineralisation and tectonic setting in the eastern Tianshan, NW China. (12th September 2019) - Wang, Yang‐Shuang; Zou, Hao; Tu, Qi‐Jun; Xu, Mo; Yang, Chang; Fu, Yu‐Zhen
Abstract : The Baishan Mo deposit in the eastern Tianshan Mountains is representative of the local metallogenic Triassic Mo belt. In this study, the geological characteristics, petrography, and geochemistry of the granite porphyry and the Mo deposit were examined using zircon U–Pb dating, molybdenite Re–Os isotope dating, whole‐rock geochemistry, and fluid inclusions. Results show that the crystallisation age of the Baishan granite porphyry is 229.8 ± 1.4 Ma and the Re–Os age of molybdenite in the ore body quartz vein is 225.0 ± 1.2 Ma. Therefore, the ore formed basically at the same time as diagenesis in the Late Triassic. The Baishan granite porphyry has high levels of Si, Al, and alkalis (K2 O + Na2 O = 5.72–8.88%) and low levels of Mg. The differentiation index is high (81.68–91.20), while the aluminium saturation index is low, indicating that the pluton belongs to metaluminous–weak peraluminous highly fractionated I‐type granite. The rock is also enriched in light rare earth elements (LREE) and large‐ion lithophile elements but depleted in heavy rare earth elements (HREE) and high‐field‐strength elements, with a distinct differentiation between LREEs and HREEs. δEu is weakly negative. The high Sr/Y and La/Yb ratios indicate geochemical characteristics similar to adakite rocks. The formation of the deposit is closely related to Mo‐rich, low‐salinity (1.23‐ to 9.73‐wt.% NaCl eqv.), and medium‐ to low‐temperature (91–280°C) magmatic fluid in the plate extension setting. The magma was derived from partial melting of thickened lower crust and possibly mixed with intrusive mantle‐derived magma. The ore‐forming fluids were uplifted, transported, mixed with meteoric water, and precipitated to form the Mo ore.